A climatology of tornado intensity assessments. (30th October 2014) - Strader, Stephen M.; Ashley, Walker; Irizarry, Ashley; Hall, Sarah
ABSTRACT An increasing number of significant and violent tornado events in the United States have been documented and mapped at extremely high resolution by government, research and private entities using remotely sensed and post‐event damage surveys; however, these assessments often generate inconsistent spatial measures of tornado strength, even for the same event. This investigation assembles a portfolio of contemporary tornado events that contain spatially comprehensive damage and/or wind velocity information from a diverse set of sources. Thereafter, the relationship between land‐use/cover and tornado intensity is examined in order to quantify spatial measures of damage indicator bias in post‐event tornado damage surveys. A climatology of both significant and violent tornado intensity assessments is then created, promoting the generation of synthetic, or model, paths with observationally constrained damage length and width metrics by the Enhanced Fujita scale magnitude. Results from the climatology and collection of synthetic paths are compared to previous observed, empirical and theoretical assessments, revealing differences in the spatial scale of the overall tornado footprint, as well as percentage contribution of swaths by Enhanced Fujita scale magnitude. The range of synthetic paths produced may be used to assess potential tornado damages to the population, the built environment and insurance portfolios.